2014
DOI: 10.1371/journal.pone.0109961
|View full text |Cite
|
Sign up to set email alerts
|

Defects in the Acquisition of Tumor-Killing Capability of CD8+ Cytotoxic T Cells in Streptozotocin-Induced Diabetic Mice

Abstract: Emerging evidences have shown that diabetes mellitus not only raises risk but also heightens mortality rate of cancer. It is not clear, however, whether antitumor CD8+ cytotoxic T lymphocyte (CTL) response is down-modulated in diabetic hosts. We investigated the impact of hyperglycemia on CTLs' acquisition of tumor-killing capability by utilizing streptozotocin-induced diabetic (STZ-diabetic) mice. Murine diabetes was induced by intraperitoneal injection of STZ (200 mg/kg) in C57BL/6 mice, 2C-T cell receptor (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 36 publications
0
5
2
Order By: Relevance
“…In vivo CD8 + T-cell proliferation and cytokine production was unaffected in diabetic C57BL/6, as was in vivo cytolytic killing. This finding is in contrast with a previous study, which demonstrated greater survival of tumour cells in STZ-induced diabetic mice [ 18 ]. It is however possible that the elevated glucose levels in diabetic mice affect not only CTL but also the tumour cells, and this may contribute to their greater survival.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In vivo CD8 + T-cell proliferation and cytokine production was unaffected in diabetic C57BL/6, as was in vivo cytolytic killing. This finding is in contrast with a previous study, which demonstrated greater survival of tumour cells in STZ-induced diabetic mice [ 18 ]. It is however possible that the elevated glucose levels in diabetic mice affect not only CTL but also the tumour cells, and this may contribute to their greater survival.…”
Section: Discussioncontrasting
confidence: 99%
“…An important point to make here is the difference between STZ protocols. Many groups administer one high dose of 200 µg/g body weight [ 18 20 ] and may see a resulting down-regulation of immune responses. STZ is a glucosamine–nitrosourea that causes DNA damage, and is particularly toxic to β-cells as it is taken up via the Glut2 transporter, which is expressed in β-cells and to a lower extent in kidney, liver and small intestine.…”
Section: Discussionmentioning
confidence: 99%
“…Further, we tested the cytotoxicity of isolated CD8 + T cells and NK cells. Recently, using melanoma model, Chen and coworkers have shown that the acquisition of tumor-killing capacity of CD8 + T cytotoxic cells is diminished in melanoma-bearing STZdiabetic mice (Chen et al 2014). However, we did not find any significant difference in cytotoxicity of CD8 + T cells to mammary tumor cells in vitro (Fig.…”
Section: Discussioncontrasting
confidence: 55%
“…Previous evidence in mice and humans clearly demonstrated the relationship between type 1 and type 2 diabetes and malignancy and some studies have investigated the underlying mechanisms (Ikemura et al 2013, Chen et al 2014. The study by Goto and coworkers demonstrated that STZ-induced diabetes accelerates mammary tumor genesis; however, the cellular basis of this effect was not explored (Goto et al 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation